Exploring User Intentions: An Investigation of Factors Influencing Digital Wallet Adoption using the Technology Acceptance Model (TAM) - Nabila, Farizka Shafa; Widodo, Arry (Journal of International Conference Proceedings, 2023)
The objective of this investigation is to scrutinise the inclinations of users towards the adoption of digital wallets. The present study involves an examination of diverse factors, namely perceived utility, ease of use, compatibility, innovation, social influence, and insecurity. Digital wallets have become an innovative payment alternative that provides users with ease, security, and easy and fast financial activities. The Bank Indonesia program GNNT (National Non-Cash Movement), which seeks to establish a cashless society, supports the use of digital wallets. However, e-wallet usage consistency remains low and unsatisfactory. The current study aims to investigate how perceived technological innovation affects the relationship between behavior intention and sustained adoption of digital wallets. This study employs the Technology Acceptance Model (TAM) theory to investigate the behavioral determinants that prompt consumers to sustain their utilization of digital wallets. It is expected that this conceptual paper will identify the factors that will help service providers in developing payment service processes using digital wallets, so that the public is more inclined to use them.Keywords: Digital Wallets, Behavioral Intention, Technology Acceptance Model, Perceived Technological Innovativeness, FinanceÂ